The Effect of Self-Control and Self-Efficacy on Academic Procrastination in Final Year Students of FKIP UNS - Wulandari, Widya Astuti; Nugroho, Jonet Ariyanto (Universitas Negeri Semarang, 2024)
This study examines the effect of self-control and self-efficacy on academic procrastination in final year students at FKIP UNS in Kentingan. This study uses quantitative research with a survey approach. The sample in this study consisted of 145 students, who were taken with a purposive sampling technique. The data collection technique used was a questionnaire, and the data analysis was done using multiple linear regression analysis. The results showed a simultaneous negative influence between self-control and self-efficacy variables on academic procrastination, as evidenced by a significance value of 0.000 (<0.05). Based on the R2 test, 40% of academic procrastination is influenced by self-control and self-efficacy. The remaining 60% is influenced by other factors outside this study is influenced by other factors such as stress levels, peer confronmation, parenting patterns, and academic control. peers, parenting patterns and control and supervision from the supervision from the family or school environment. The findings of this study can be used as recommendations for the university to help final year students to avoid academic procrastination so that they can graduate on time.